Le système monétaire européen : Un point de vue nord américain - Fortin, L.; Perron, Martin (Études internationales, 1981)
Is the european monetary System (EMS) a useful approach to the problems it is meant to solve and to the pursuit of the objectives that its promoters have set for themselves? A review by the authors of a number of economic motives which underly the creation of the EMS leads them to conclude that the various economic problems which the european readily blame on floating exchange rates find in fact their origins in the economic policies pursued by the national governments. Moreover, the authors consider that the defense of parities in the EMS, either through intervention in the exchange markets or by other means, can involve high economic costs and that in the longer run market forces always triumph when parities no longer reflect the fundamental positions of the respective economies. Among the other factors which limit the usefulness of the EMS the authors identify the continuing lack of macro-economic policy coordination by participating countries, its regional character, the underestimation of the importance of the american dollar in the international monetary system and the impact of its fluctuations on european currencies and the tendency of the EMS to harmonize inflation rates at a higher level than should be aimed for. The authors therefore conclude that it is doubtful that the EMS constitutes a useful instrument of economic policy and that efforts towards european monetary union based on such a system of parities can be successful under present circumstances.